Modelling of electric arc furnace off-gas removal system. (May 2014) - Timoshenko, N.; Semko, A.; Timoshenko, S.
Abstract : A mathematical model of an electric arc furnace off-gas removal system, aimed at improving the energy efficiency of the smelting process, was created and verified by methods of physical modelling and numerical simulations. For an industrial-scale furnace, equipped with annular distributing off-gas suction system, the possibility to reduce fugitive emissions by 40%, air inflow by 24%, total emissions by 13% and the melting dust removal by 33% was shown. The obtained data will allow, according to estimations, specific energy consumption to reduce by at least 16–20 kW h t −1 and increase the environmental performance of the furnace.